Glacial Lake Area Change and Potential Outburst Flood Hazard Assessment in the Bhutan Himalaya - Rinzin, Sonam; Zhang, Guoqing; Wangchuk, Sonam (Frontiers in Earth Science, 2021)
Against the background of climate change-induced glacier melting, numerous glacial lakes are formed across high mountain areas worldwide. Existing glacial lake inventories, chiefly created using Landsat satellite imagery, mainly relate to 1990 onwards and long (decadal) temporal scales. Moreover, there is a lack of robust information on the expansion and the GLOF hazard status of glacial lakes in the Bhutan Himalaya. We mapped Bhutanese glacial lakes from the 1960s to 2020, and used these data to determine their distribution patterns, expansion behavior, and GLOF hazard status. 2187 glacial lakes (corresponding to 130.19km2) were mapped from high spatial resolution (1.82−7.62 m), Corona KH-4 images from the 1960s. Using the Sentinel-2 (10 m) and Sentinel-1 (~22 m), we mapped 2553 (151.81 ± 7.76 km2), 2566 (152.64 ± 7.83 km2), 2572 (153.94 ± 7.83 km2), 1569 (153.97 ± 7.79 km2) and 2574 (156.63 ±7.95 km2) glacial lakes in 2016, 2017, 2018, 2019 and 2020, respectively. These glacial lakes were mainly present in the Phochu (20.66 %) and the Kurichu (20.66%) basins. A total of 157 glacier-fed lakes have changed into non-glacier-fed lakes over the ~60 years of lake evolution. Glacier-connected lake area growth accounted for 75.4% of the total expansion, reaffirming the dominant role of glacier-melt water in expanding glacial lakes. Between 2016 and 2020, 19 (4.82 km2) new glacial lakes were formed with an average annual expansion rate of 0.96 km2 per year. We identified 31 lakes with a very-high and 34 with high GLOF hazard levels. These very-high to high GLOF hazard lakes were primarily located in the Phochu, Kurichu, Drangmechu, and Mochu basins. Increasing glacier melt resulting from water warming is the possible driver of glacial lake expansion as precipitation was decreasing in the region. Our results imply that extending glacial lakes studies back to the 1960s provides new insights on glacial lake evolution from glacier-fed lakes to non-glacier-fed lakes. Additionally, we reaffirmed the capacity of Sentinel-1 and Sentinel-2 data to determine annual glacial lake changes. The results from this study are can be a valuable basis for future glacial lake monitoring and prioritizing limited resources for GLOF mitigation programs.